2001
DOI: 10.1080/00288306.2001.9514938
|View full text |Cite
|
Sign up to set email alerts
|

Extensional fault kinematics within the Taupo Volcanic Zone, New Zealand: Soft‐linked segmentation of a continental rift system

Abstract: The Taupo Volcanic Zone (TVZ) is a young (<2 Ma) arc-backarc system in continental crust at the southern end of the Havre Trough characterised by intense volcanism and geothermal activity. An extensional fault belt (known locally as the Taupo Fault Belt) can be traced semicontinuously within the TVZ from Ruapehu in the southwest to the Bay of Plenty coast in the northeast. Contained within the belt are numerous active volcanic centres (andesitic, basaltic, rhyolitic) and geothermal systems. Kinematic studies d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(143 citation statements)
references
References 38 publications
5
138
0
Order By: Relevance
“…A similar change was observed before and after the 1992 eruptions of Crater Peak vent, Mt Spurr, Alaska, from detailed analysis of earthquake focal mechanisms (Roman et al 2004). At Ruapehu this change was attributed to a magmatic intrusion along a northeast-southwest-oriented dike system that resulted in a northwest-southeast compressive stress, the reverse of the northwest-southeast extension normally expected in this area (Rowland & Sibson 2001). At Mt Spurr the stress change was strongly localised and did not extend as far as 10 km from the eruption site (Roman et al 2004), but at Ruapehu stress changes were observed over an area of at least 10 × 10 km (Gerst & Savage 2004).…”
Section: Western Taranakimentioning
confidence: 72%
See 1 more Smart Citation
“…A similar change was observed before and after the 1992 eruptions of Crater Peak vent, Mt Spurr, Alaska, from detailed analysis of earthquake focal mechanisms (Roman et al 2004). At Ruapehu this change was attributed to a magmatic intrusion along a northeast-southwest-oriented dike system that resulted in a northwest-southeast compressive stress, the reverse of the northwest-southeast extension normally expected in this area (Rowland & Sibson 2001). At Mt Spurr the stress change was strongly localised and did not extend as far as 10 km from the eruption site (Roman et al 2004), but at Ruapehu stress changes were observed over an area of at least 10 × 10 km (Gerst & Savage 2004).…”
Section: Western Taranakimentioning
confidence: 72%
“…These will tend to occur normal to the extension direction (Nakamura 1977), and vent alignment has been used in the southern Taupo Volcanic Zone for estimating the extension direction (Rowland & Sibson 2001). The overall SSE migration of the Taranaki volcanoes since 1.74 Ma is not compatible with a northwest-southeast S^ suggested by the orientation of the CEFZ.…”
Section: Western Taranakimentioning
confidence: 99%
“…Transfer fault zone geometries may change, or be abandoned, during linkage (e.g., Morley and Nelson, 1990;Schlische, 1993;Cartwright et al, 1995;Densmore et al, 2007). The role of magmatism in segment linkage during the spe 500-11 1st pgs page 5 early rifting stages remains poorly understood owing to the general lack of detailed subsurface data (e.g., Ebinger et al, 1989;Rowland and Sibson, 2001), but clear patterns are seen in mature rift zones, as outlined below.…”
Section: Along-axis Segmentationmentioning
confidence: 99%
“…1). The tectonic structure has been defined as the Taupo Rift (Acocella et al 2002;Villamor & Berryman 2006), Taupo Fault Belt (TFB, Berryman & Villamor 1999, or Ruaumoko Rift (Rowland & Sibson 2001). At some latitudes along the Tauo Rift, such as near Ruapehu and to the south of Rotorua, the faults form a welldefined graben structure in the centre of the zone.…”
Section: The Taupo Riftmentioning
confidence: 99%